2016
DOI: 10.1016/j.prro.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Risk of radiation pneumonitis in patients receiving taxane-based trimodality therapy for locally advanced esophageal cancer

Abstract: Purpose There are limited data regarding clinical and treatment factors associated with radiation pneumonitis (RP) in patients receiving Taxane-based tri-modality therapy for esophageal cancer. The purpose of this study was to identify predictors of RP in patients undergoing tri-modality therapy. Materials and Methods We retrospectively reviewed patients undergoing chemoradiation followed by esophagectomy between 2006-2011. The association between clinical and dosimetric factors with RP was assessed using Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
3
14
0
3
Order By: Relevance
“…Tanabe et al performed a retrospective study of 86 EC patients undergoing definitive chemoradiotherapy, and found that the V 5Gy and V 10Gy values were the only factors significantly correlated with grade 2 or higher RP . Similarly, Shaikh et al also reported that V 5Gy and V 10Gy were strong predictors of symptomatic RP in a cohort of 139 EC patients treated with chemoradiotherapy and concluded that minimizing the low dose spread to the lung can decrease the risk of RP for these patients . In this study, the FJT plans significantly reduced the volume of the lung treated at each dose level (5–40 Gy), especially below 13 Gy.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Tanabe et al performed a retrospective study of 86 EC patients undergoing definitive chemoradiotherapy, and found that the V 5Gy and V 10Gy values were the only factors significantly correlated with grade 2 or higher RP . Similarly, Shaikh et al also reported that V 5Gy and V 10Gy were strong predictors of symptomatic RP in a cohort of 139 EC patients treated with chemoradiotherapy and concluded that minimizing the low dose spread to the lung can decrease the risk of RP for these patients . In this study, the FJT plans significantly reduced the volume of the lung treated at each dose level (5–40 Gy), especially below 13 Gy.…”
Section: Discussionsupporting
confidence: 51%
“…However, IMRT is generally associated with a larger volume of low‐dose spread to normal tissues, in part due to the transmitted radiation through the multileaf collimator (MLC) . Clinical studies have found that the volumes of the lung receiving low doses were strongly associated with the incidence of radiation pneumonitis (RP), which is a major concern for EC patients receiving radiotherapy. It may not only cause serious pulmonary injury but also limit dose escalation strategies .…”
Section: Introductionmentioning
confidence: 99%
“…2 The limitations of VMAT and IMRT are especially concerning when treating lung tumors because large volumes of low-dose radiation increase the risk of pneumonitis and esophagitis. 7,8,20,21 IMRT has shown reduced rates of pneumonitis compared to 3D-CRT. 22,23 The Radiation Therapy Oncology Group (RTOG) 0617 trial showed significantly higher rates of severe pneumonitis in patients treated with 3D-CRT compared to IMRT (7.9% vs 3.5%, P ¼ .046), and the V20 may be more predictive of the risk of pneumonitis than the V5.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of 11 RA plans had an esophageal V60 >17%. Shaikh et al reported that the risk of radiation pneumonitis is significantly increased with a lung V5 >65% and a V20 >25%, 21 while secondary analysis of RTOG 0617 indicates that V20 is more predictive of radiation pneumonitis risk. 22 In the H-RA and RA plans in our study, 9 of 11 had a V20 !25%, whereas the V20 was !25% for all 11 of the 3D-CRT plans.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous study reported that using HT for CEC increases low-dose radiation in the lung compared to that by 3DCRT due to lateral directional beamlets that traverse both sides of the lung during gantry rotations [ 10 ]. Although the rate of radiation pneumonitis (RP) in CEC has not been determined, it is a common adverse event in thoracic oesophageal cancer, and low-dose irradiated lung volumes such as V5 and V10 have been reported as important predictive factors for RP [ 11 13 ]. An HT function termed “block plan” can restrict beamlets by using a virtual block during computation of dose optimization and may aid in dose reduction.…”
Section: Introductionmentioning
confidence: 99%